Fatal Case of Invasive Pulmonary Aspergillosis Post COVID-19 Pneumonia Due to Aspergillus Niger - Noori, Zaid (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.